Anthropometric and lifestyle characteristics of active and inactive saudi and british adolescents. Issue 5 (17th June 2014) - Duncan, Michael J.; Al‐hazzaa, Hazzaa M.; Al‐Nakeeb, Yahya; Al‐Sobayel, Hana I.; Abahussain, Nada A.; Musaiger, Abdulrahman O.; Lyons, Mark; Collins, Peter; Nevill, Alan
Abstract : Objectives: To compare the anthropometric and lifestyle characteristics of active and inactive adolescents in Saudi Arabia and Britain. Methods: A school‐based cross‐sectional study was conducted at four cities in Saudi Arabia (Riyadh and Al‐Khobar; N  = 1, 648) and Britain (Birmingham and Coventry; N  = 1, 158). The participants (14‐ to 18‐year‐olds) were randomly selected using a multistage stratified cluster sampling. Measurements included anthropometric [BMI, Waist circumference (WC), Waist to height ratio], screen time, validated physical activity questionnaire and dietary habits. Results: British males were lighter ( P  = 0.04, 64.4 vs. 68.2 kg), and had lower values for WC ( P  = 0.003, 77.1 vs. 78.7 cm) than Saudi males. Males ( P  = 0.0001) were significantly more active than females but the difference between inactive Saudi and British females was greater than that between inactive Saudi and British males. Being female was significantly ( P  < 0.001) associated with lower activity levels in both the Saudi and British adolescents. Having lower frequency of fruit intake was significantly ( P  < 0.001) associated with lower activity levels, whereas increased frequency of consumption of French fries/potato chips was significantly ( P  = 0.008) associated with increased activity levels in Saudi adolescents. Among British adolescents, lower frequency of breakfast was ( P  = 0.045) associated with lower activity levels, increased frequency of consumption of sweetened beverages was significantly ( P  = 0.005) associated with higher activity levels. Higher energy drinks intake frequency was significantly ( P  = 0.007) associated with higher activity levels. Conclusion: The present study identifies crosscultural differences and similarities in lifestyle habits in adolescents from Britain and Saudi Arabia. Activity status (active vs. inactive) appears to play an important role in other lifestyle related behaviors, with active adolescent more likely to engage in healthy dietary behavior than their inactive peers, irrespective of country of origin. Am. J. Hum. Biol. 26:635–642, 2014. © 2014 Wiley Periodicals, Inc.